Impact of Aluminum Oxide Content on the Structural and Optical Properties of ZnO: AlO Thin Films - Abass, Hawraa Hadi; Hasan, Bushra A (Iraqi Journal of Physics, 2021)
AlO-doped ZnO nanocrystalline thin films from with nano crystallite size in the range (19-15 nm) were fabricated by pulsed laser deposition technique. The reduction of crystallite size by increasing of doping ratio shift the bandgap to IR region the optical band gap decreases in a consistent manner, from 3.21to 2.1 eV by increasing AlO doping ratio from 0 to 7wt% but then returns to grow up to 3.21 eV by a further increase the doping ratio. The bandgap increment obtained for 9% AlO dopant concentration can be clarified in terms of the Burstein–Moss effect whereas the aluminum donor atom increased the carrier’s concentration which in turn shifts the Fermi level and widened the bandgap (blue-shift). The engineering of the bandgap by low concentration of AlO dopant makes ZnO: AlO thin films favorable for the fabrication of optoelectronic devices. The optical constants were calculated and was found to be greatly affected by the increasing the doping ratio.